The Clinical Accuracy and Risk Stratification in End of Therapy 18F-FDG PET/CT in Burkitt Lymphoma - Mo, Yi Wen; Xiao, Zi Zheng; Wei, Yuan; Li, Xin Ling; Zhang, Xu; Fan, Wei (Frontiers in Oncology, 2021)
Purpose Burkitt lymphoma (BL) is an invasive lymphoma subtype with FDG avid at 18F-FDG PET/CT, but there is currently no validated criterion in treatment evaluation and prognosis prediction. The aim of this study was to analyze the clinical accuracy of 18F-FDG PET/CT in Burkitt lymphoma in end of therapy PET/CT (EOT-PET) to assess the treatment response in BL and conduct a survival analysis with different Deauville 5-point score (DS) cutoff values. Materials and Methods A total of 189 patients were retrospectively included: 97 underwent baseline PET/CT and all underwent EOT-PET. Survival curves were plotted according to the Kaplan-Meier method. Different DS cutoff values in EOT-PET were evaluated for risk stratification in Burkitt lymphoma. Results The median progression free survival (PFS) and overall survival (OS) were 52 and 53 months, respectively. Applying the conventional DS 4 to 5, there was significant difference in outcome between EOT-PET negative and positive patients. However, the positive predictive value (PPV) (28.3% for PFS and 26.4% for OS) is low despite a high negative predictive value (NPV) (94.1% for OS and 94.9% for OS). When we moved the cutoff point to DS 5, the PPV was improved evidently (88.2% for PFS and 82.3% for OS) with the satisfactory NPV simultaneously (95.3% for PFS and 95.9% for OS). Conclusions EOT-PET results using DS significantly related with PFS and OS. DS of 5 may be a better cutoff point at the end of treatment to determine whether patients have a significant risk of recurrence or progress.